The developmental objectives (Maqasid) of zakah - Eletrebi, Mohamed Fathy; Suleiman, Hassan; Abdul Aziz, Mohammad Najmuddin (Lembaga zakat Negeri Kedah, 2019)
Zakāh is monetary ‘ibādah (Islamic ritual) and considered to be a primary resource and distribution of a state in facing problems of the community, importantly with regards to poverty and its types. Being an obligatory ‘ibādah ordained by Allah, it is considered to be a form of trial and test upon mankind unto something which they immensely love. Thus, the relevance of this topic prevails when discussing on the governance of Zakāh fund, its development and orientation as intended by Allah. Development of Ẓakāh funds in Malaysia with particular reference to Ẓakah institution in Kedah. This research determines to understand the developmental role of Zakāh in curbing poverty and relative poverty with special reference to Malaysia community. The research undertakes descriptive analytical method to expound on the role of Zakāh in curbing poverty in Malaysia through its application by Zakāh institution in the state of Kedah. Zakāh as a monetary resource of a state, magnifies the splendor of Sharī’ah and its perfection in interacting with the second rule of a state, which is wealth. Zakāh plays a big role in developing community and curb its problems, particularly the problem of poverty and relative poverty.